الضبط الإداري وأثره على الحريات العامة - حوامد, عبد الحكيم (جامعة الوادي.University eloued, 2021)
أما الانعكاسات السلبية فهي تعتبر تهديدا وخطرا على الحريات العامة ومنا لها استنادا السلطة العسكرية مسؤولية الحفاظ على النظام العام و بالتالي تعطيل العمل بالدستور .الذي يكفل حقوق وحريات الإفراد وعموما فهذه الآثار السلبية تكون نتيجة للإجراءات التي تكون الغاية منها مواجهة الحالة الاستثنائية مما يعني تكون على حساب الحريات العامة للإفراد As for the negative repercussions, they are considered a threat and a danger to public liberties, and the military authority has the responsibility to maintain public order and thus disrupt the work of the constitution, which guarantees the rights and freedoms of individuals. In general, these negative effects are the result of measures whose purpose is to confront the exceptional situation, which means that they are at the expense of the public freedoms of individuals
قانون اداري
Keywords: الضبط الإداري ،الحريات العامة; Dispositions générales - Immobilier - Législation algérienne